Extraction methods of essential oil from kaffir lime (Citrus hystrix): A review / Suhaila Mohd Sauid and Faris Azri Aswandi - Mohd Sauid, Suhaila; Aswandi, Faris Azri (Universiti Teknologi MARA Shah Alam, 2018)
Essential oil is a valuable product in various industries but unfortunately, it is scarce. Various extraction methods currently being used to obtain the essential oil from kaffir lime leaves (Citrus hystrix), however, to date, best extraction methods are yet to be concluded. This review paper highlights the production yield, pros and cons of various kaffir lime leaves essential oil extraction methods available in present research papers albeit limited to lab scale. Each methodology has their own advantages and disadvantages, so it is not possible to say that one method is the best. This review also covers the pre-treatment processes as since they can significantly affect the performance of other important processes as well as the production yield. In conclusion, each of the extraction and pre-treatment method has its own pros and cons, hence selecting a suitable method depend heavily on the producer’s requirements.